Education and Culture Crises in the Early Twenty-First Century World - شارل ولوتر (Comparative Education Society of Iran ( CESIR), 2018)
The thesis of this paper is that while culture as it appears in the world of the early twenty-first century, is radically different than was the case in all earlier centuries; schools and education systems worldwide still reflect the templates upon which they were built in eras past, and are not aligned with the realities and exigencies of the contemporary world as regards culture.  The paper traces the beginning of schools in the ancient world, and how, according to the Cohen hypothesis, schools began to foist down a uniform, dominant culture. After the creation of mass systems of public schooling, school systems have still been serving as agents of cultural hegemony. However current demographic and social trends have coincided to create increasingly diverse societies; and current political, economic and life-philosophical contextual imperatives ask for an appreciation of diversity, and in such a context, inherited school systems appear to be more and more an anachronism. How education should be reformed in view of the new exigencies, form the concluding section of the paper.